Single-Walled Carbon Nanotubes with Red Phosphorus in Lithium-Ion Batteries: Effect of Surface and Encapsulated Phosphorus - Anna A. Vorfolomeeva; Svetlana G. Stolyarova; Igor P. Asanov; Elena V. Shlyakhova; Pavel E. Plyusnin; Evgeny A. Maksimovskiy; Evgeny Yu. Gerasimov; Andrey L. Chuvilin; Alexander V. Okotrub; Lyubov G. Bulusheva (Nanomaterials, 2022)
Single-walled carbon nanotubes (SWCNTs) with their high surface area, electrical conductivity, mechanical strength and elasticity are an ideal component for the development of composite electrode materials for batteries. Red phosphorus has a very high theoretical capacity with respect to lithium, but has poor conductivity and expends considerably as a result of the reaction with lithium ions. In this work, we compare the electrochemical performance of commercial SWCNTs with red phosphorus deposited on the outer surface of nanotubes and/or encapsulated in internal channels of nanotubes in lithium-ion batteries. External phosphorus, condensed from vapors, is easily oxidized upon contact with the environment and only the un-oxidized phosphorus cores participate in electrochemical reactions. The support of the SWCNT network ensures a stable long-term cycling for these phosphorus particles. The tubular space inside the SWCNTs stimulate the formation of chain phosphorus structures. The chains reversibly interact with lithium ions and provide a specific capacity of 1545 mAh·g−1 (calculated on the mass of phosphorus in the sample) at a current density of 0.1 A·g−1. As compared to the sample containing external phosphorus, SWCNTs with encapsulated phosphorus demonstrate higher reaction rates and a slight loss of initial capacity (~7%) on the 1000th cycle at 5 A·g−1.